Development of an Alkaloid-Pyrone Annulation: Synthesis of Pleiomaltinine - Ziegler, Robert E.; Tan, Shin Jowl; Kam, Toh Seok; Porco, John A. (John Wiley & Sons, 2012)
Odd Couple: A method for the synthesis of alkaloid-pyrones using a novel pyrone annulation of β-carbolines and indoles with 3-siloxy-4-pyrones is reported. The approach has enabled synthesis of the unusual alkaloid-pyrone pleiomaltinine from the plant-derived indole-alkaloid pleiocarpamine (see Scheme; TBS= tert-butyldimethylsilyl). © 2012 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.